Physico-Chemical and Microbiological Safety of Water Utilized in the Medical Cell, Mbarara City, Southwestern Uganda, a Cross-Sectional Study - Okeny, Christopher; Kiduuma, Wilson; Ikiiriza, Adrine; Sonia, Salim S; Omara, Sadrack; Abaasa, Catherine N (Student's Journal of Health Research Africa, 2023)
Introduction: Safe and readily available water is very vital for public health functions whether it is used for drink- ing, food production, washings, or recreation purposes. This study assessed the physical properties (temperature, total dissolved solids), chemical properties (pH, electrical conductivity), and microbi- ological properties (total coliform counts, Escherichia coli counts) of domestic water utilized in the medical cell, Mbarara city, Southwestern Uganda. Method: Total coliform counts and total Escherichia coli counts were performed on Eosin Methylene blue medium and the organisms were subculture on MacConkey agar. This was followed by biochemical tests on individual bacterial colonies to identify the water contaminant. Results: The study revealed that temperature ranged from 21.3oC to 25.5oC, pH ranged from 5.23 to 7.91, electrical conductivity ranged from 110 to 189μS/cm, and total dissolved solids ranged from 54mg/dl to to112mg/dL. Microbiologically, 67.74% of the water samples had total coliform counts >10CFU/100mL and 6.45% had Escherichia coli counts > 0CFU/100mL of the water sample. 47.62% of the iso- lates were Enterobacter spp, 38.10% Citrobacter spp, 9.52% Escherichia coli, 9.52% Klebsiella spp, 7.14% Salmonella spp and 4.76% Pseudomonas spp. Conclusion: Microbiologically, water supply had potential disease-causing pathogens which pose risks of water- borne disease outbreak to the population. Recommendation: The national water and sewerage corporation should inspect the water supply pipelines for leakages and repairs should be made where necessary. Responsible stakeholders of the Medical cell, Mbarara City should ensure proper disposal of human wastes. Further studies can be done to genotype the microbial water contaminants and or determine their antimicrobial susceptibility patterns.
Keywords: Physical; Chemical; Microbiological; Safety; Domestic; Water